Lightweight and broadband NiO/Ni/borophene foams for enhanced electromagnetic wave attenuation - Dizayee, Wala; Mohammed, Mohammed Ahmed; Zorah, Mohammed; Mahmoud, HassabAlla M.A.; Abdulnabi, Mohamed Shabbir; Abdulkareem-Alsultan, G.; Nassar, Maadh Fawzi (Elsevier, 2025)
The development of high-performance microwave absorbing materials poses a significant challenge due to the complex balance required between dielectric and magnetic losses, structural integrity, and impedance matching. Conventional NiO/Ni composites, though promising, face several limitations Nickel demonstrates significant magnetic loss but inadequate impedance matching, whereas nickel oxide, functioning as a dielectric, provides minimal attenuation and restricted conductivity. Moreover, particle aggregation, elevated material density, and limited absorption bandwidth further constrain their utility in contemporary electromagnetic interference (EMI) shielding systems. This study presents a unique 3D hierarchical NiO/Ni/Borophene (NNB) nanocomposite synthesized by a scalable, solution-based method to address these inherent limitations. Borophene, a lightweight, metallic, and anisotropically conductive two-dimensional substance, serves as a structural and functional enhancer. Its integration accelerates charge transport, increases dielectric loss through interfacial polarization, and facilitates impedance matching by reducing excessive conductivity. The freeze-dried design presents a foam-like structure that enhances multiple scattering and effectively attenuates incident waves. Of the compositions analyzed, NNB-20 (20 wt % borophene) demonstrated superior performance, with a minimum reflection loss of −55.5 dB at 12.8 GHz and a wide absorption bandwidth. This study emphasizes borophene's synergistic roles in overcoming the limitations of traditional NiO/Ni systems, establishing NNB nanocomposites as a novel category of lightweight, broadband, and high-efficiency microwave absorbers for sophisticated EMI shielding applications.